Translation and determining the validity and reliability of the nordic orofacial test-screening in children with and without orofacial dysfunction - ghazi, shamim; Hosseini, Horia; Babajanzade, Parisa; Azimi, Tabassom; Khafri, Soraya (World Nutrition, 2025)
Background Orofacial skills include vital activities such as breathing, chewing, swallowing, social interactions and speech, which have a significant impact on people’s quality of life. Nordic Orofacial Test-Screening (NOT-S) is a tool for evaluating speech, chewing and swallowing problems in children over 3 years old. Objective The aim of the present study is to investigate the psychometric characteristics of the NOT-S. Methods A descriptive-analytical design is used in this study, which is a foundation method type. The oral-facial evaluation tool NOT-S was translated and equated into Persian. Based on expert opinion, the content and form validity of this tool were determined. To investigate test-retest reliability and internal consistency, the test was conducted on 25 children with orofacial dysfunction and 30 children without orofacial dysfunction aged 3 to 6 years, with an average age of 4.98±±1.42 from the city of Babol. Impact score, content validity index (CVI), content validity ratio (CVR), Cronbach’s alpha, and intracluster correlation coefficient were calculated. Results In face validity check, the impact score of all items was higher than 2.52. In content validity, the CVI of each item was higher than 81% and the CVR of all items was higher than 50%. The intra-cluster correlation coefficient was estimated at 0.998 and 0.948 in the interview and evaluation sections, respectively, which is statistically significant according to Landy and Koch’s classification. The Cronbach’s alpha coefficient of the whole instrument was 0.77. Conclusions We thus found that the Persian version of the orofacial abilities assessment tool is acceptable in terms of validity and reliability for Persian-speaking children with and without orofacial dysfunction.